Kemampuan Guru Dalam Mengimplementasikan Model Cooperative Learning Tipe STAD Pada Subtema Indahnya Keragaman Budaya Negeriku Di Kelas IV SD Negeri 62 Banda Aceh - maulidia, miska; Nurhaidah, Nurhaidah; Mislinawati, Mislinawati (Universitas Syiah Kuala, 2022)
The purpose of the study was to describe the teacher's ability to implement the STAD type cooperative learning model on the theme of 7 sub-themes 2 PB 2 in the fourth grade of SD Negeri 62 Banda Aceh. The approach in this study is a qualitative approach using a descriptive type of research. The subjects in this study were 3 fourth-grade teachers. Data collection techniques using observation techniques, and interviews. All data from observations and interviews were processed using the data analysis stages, namely, data reduction, data presentation, and drawing conclusions. The results of this study show that the teacher's ability to implement the STAD type cooperative learning model has 7 sub-themes 2 PB 2 in grade IV SD Negeri 62 Banda Aceh which is included in the very capable category, this is indicated by the value range of 85% - 100%. students are actively involved in the learning process both in groups and individually. The conclusion of this study is that teachers at SD Negeri 62 Banda Aceh have been able to apply the STAD type of cooperative learning model according to the steps contained in the learning model.